THE EFFECT OF EMO-DEMO TRAINING ON KNOWLEDGE AND SKILLS OF POSYANDU CADRES ON 'ASI ONLY ENOUGH' - Andriana Andriana; Elvira Junita; Evi Kristina; Rika Herawaty; Yuyun Bewelli Fahmi (Universitas Negeri Gorontalo, 2022)
Stunting has a big impact on the growth and development of children. Posyandu cadres, spearheading health services in the community, have a role in increasing exclusive breastfeeding coverage. The Emo Demo method is an imaginative and provocative way to achieve behavior change in the field of public health. The purpose of the study was to determine the effect of Emo-Demo training on the knowledge and skills of posyandu cadres about breastfeeding in Sungai Kumango Village, Tambusai District. This research method is quasi-experimental with pretest-posttest design, total sampling technique, dependent t test. The results showed that posyandu cadres had never known counseling techniques using the emo-demo method, pretest knowledge was in good category (40%), posttest knowledge was in good category (80%), pretest cadre skills were in good category (33.3%), pretest cadre skills with good category (67.7%). The conclusion of the study is that there are differences in the knowledge of cadres about breastfeeding only before and after training, the value of p = 0.000 (0.05) and there are differences in the skills of cadres in providing counseling about breastfeeding only before and after training, the value of p = 0.000 (0.05).The emo demo method can increase the knowledge and skills of posyadu cadres in providing counseling about breastfeeding. Keywords: Emo-Demo, Cadre, Skills, Knowledge